Quest for Female Identity: A Feminist Study of Shashi Deshpande’s Selected Novels - Muhammad Afzal (University of Chitral Journal of Linguistics and Literature, 2021)
Shashi Deshpande’s novels deal with traditional and patriarchal Indian set up as well as the difficulties faced by women handling multiple roles in Indian society. Deshpande’s protagonists belong to typical middle-class family and are caught in the web of traditional patriarchy, set by ideology in one hand and with the desire of independent identity on the other way. All the women characters of Deshpande's fiction try to assert themselves both within and without the familiar zones by overcoming the challenges and hindrances and have proved their individuality and unique identity as human beings by taking decisions on their own through suffering and enlightenment. Moreover, the present research is qualitative in its approach that is conducted under the feminist theoretical perspectives.